2023
DOI: 10.1590/fst.103122
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, and bioactivities of polysaccharides fractions from sugarcane leaves

Abstract: Three new polysaccharides (SLP-50, SLP-70, and SLP-90) were fractionated successively by gradient concentrations of ethanol. This study aimed to investigate the initial structural characterization and bioactivities of these sugarcane leaves polysaccharides (SLPs) obtained by ultrasound-assisted extraction. The results, which were further validated by IR spectrometry, revealed that the three SLPs contained uronic acids, proteins, and sulfate groups in addition to carbohydrate. SLP-50 (36.40 kDa), SLP-70 (12.97 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Traditional Chinese medicine also recognizes non‐centrifuge sugar for its reputed benefits in relieving cough, promoting bowel movements, and mitigating adverse effects of alcohol. Modern medical research has further confirmed the anticavity (Jaffé, 2012), antioxidant (Xu et al., 2005), antibacterial (Kaur et al., 2017), anti‐inflammatory (Ledon et al., 2003), hypoglycemic (Mo et al., 2023), and antitumor effects (Prakash et al., 2021) of non‐centrifuge sugar.…”
Section: Introductionmentioning
confidence: 96%
“…Traditional Chinese medicine also recognizes non‐centrifuge sugar for its reputed benefits in relieving cough, promoting bowel movements, and mitigating adverse effects of alcohol. Modern medical research has further confirmed the anticavity (Jaffé, 2012), antioxidant (Xu et al., 2005), antibacterial (Kaur et al., 2017), anti‐inflammatory (Ledon et al., 2003), hypoglycemic (Mo et al., 2023), and antitumor effects (Prakash et al., 2021) of non‐centrifuge sugar.…”
Section: Introductionmentioning
confidence: 96%